2014
DOI: 10.15249/6-2-28
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility for SMEs: A proposed hypothesised model

Abstract: In a competitive, globalised world, corporate social responsibility (CSR) is proposed as a strategy to invigorate the competitiveness of small-and medium-sized enterprises (SMEs). The primary objective of this paper is to identify CSR factors that influence the competitiveness of SMEs and to develop a hypothesised model that can be tested on SMEs. Although SMEs in Uganda are increasingly becoming the backbone of the economy, their rate of survival and competitiveness are a cause for concern. The outcomes of CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Studies have distinguished four different types of CSR activities. First, environmentally related CSR activities refer to measures a business entity can take to minimise its negative impact on the natural environment, such as using environmentally friendly packaging, recycling, waste reduction, energy and water conservation, and pollution control (Turyakira et al, 2012(Turyakira et al, , 2014. Next, socially oriented CSR activities relate to both employee and society oriented CSR activities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have distinguished four different types of CSR activities. First, environmentally related CSR activities refer to measures a business entity can take to minimise its negative impact on the natural environment, such as using environmentally friendly packaging, recycling, waste reduction, energy and water conservation, and pollution control (Turyakira et al, 2012(Turyakira et al, , 2014. Next, socially oriented CSR activities relate to both employee and society oriented CSR activities.…”
Section: Introductionmentioning
confidence: 99%
“…Third, studies have differentiated employee-oriented CSR activities, which refer to those activities aimed at improving the working conditions of workers such as: offering training and development, workplace diversity, and helping workers to maintain a work-life balance (Turyakira et al, 2012(Turyakira et al, , 2014. Finally, society oriented CSR activities refer to the activities aimed at helping the community through for instance sponsoring sports and education, provision of healthcare, assistance to low-income groups, and participation in community activities (Turyakira et al, 2012(Turyakira et al, , 2014. Turyakira et al (2012) pointed out that SMEs are mainly active in environmentally and socially related CSR activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CSR on which this paper focuses is the type defined from a generic perspective that applies to all organisations, irrespective of the type of business they do and the industry or sector to which they belong. This type of CSR is defined as any organisation's concern for its own survival, for the community it serves and for the environment in which it operates (Katamba et al, 2014(Katamba et al, , 2012Turyakira et al, 2012;Albareda et al, 2006). In this context, CSR is not a requirement or even a role; it is regarded as a form of 'concern for others' expressed as a responsibility to do business right, judiciously while exercising generosity that does not hurt it (Katamba & Nkiko, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most common examples of CSR in SMEs include donating to local causes and charities, sponsorship of local events and organizations, support for local schools colleges, environmental initiatives, ethical purchasing and staff related activities (Worthington et al, 2006). The nature of CSR activities in SMEs can be significantly different from those activities in large enterprises, for example: the relationships between SMEs and their key stakeholders (especially employees and customers) are characterized by a high level of informality, relations with customers who are usually depend on personal knowledge of customer's needs, while relations with employees are more family like(Turyakira et al, 2013) as they are generally living in the same place Mandl and Dorr (2007). demonstrated that CSR activities in SMEs are particularly focused on market-orientated, workforce-orientated, society-orientated, and environment-orientated.…”
mentioning
confidence: 99%